Blocking of the Alpha Interferon-Induced Jak-Stat Signaling Pathway by Japanese Encephalitis Virus Infection - Lin, Ren-Jye (American Society for Microbiology, 2004)
The induction of alpha/beta interferon (IFN-α/β) is a powerful host defense mechanism against viral infection, and many viruses have evolved strategies to overcome the antiviral effects of IFN. In this study, we found that IFN-α had only some degree of antiviral activity against Japanese encephalitis virus (JEV) infection, in contrast to another flavivirus, dengue virus serotype 2, which was highly sensitive to IFN-α in the cultured cell system. JEV infection appeared to render cells resistant to IFN-α since the IFN-α-induced luciferase reporter activity driven by the IFN-stimulated response element (ISRE) was gradually reduced as the JEV infection progressed. Since the biological activities of IFNs are triggered by the Janus kinase (Jak) signal transducer and activation of transcription (Stat) signaling cascade, we then studied the activation of Jak-Stat pathway in the virus-infected cells. The IFN-α-stimulated tyrosine phosphorylation of Stat1, Stat2, and Stat3 was suppressed by JEV in a virus replication and de novo protein synthesis-dependent manner. Furthermore, JEV infection blocked the tyrosine phosphorylation of IFN receptor-associated Jak kinase, Tyk2, without affecting the expression of IFN-α/β receptor on the cell surface. Consequently, expression of several IFN-stimulated genes in response to IFN-α stimulation was also reduced in the JEV-infected cells. Overall, our findings suggest that JEV counteracts the effect of IFN-α/β by blocking Tyk2 activation, thereby resulting in inhibition of Jak-Stat signaling pathway.